Changes in Age Stereotypes in Adolescent and Older Participants of an Intergenerational Encounter Program - Kranz, Dirk; Thomas, Nicole Maria; Hofer, Jan (Frontiers in Psychology, 2021)
This intervention study explored the effects of a newly developed intergenerational encounter program on cross-generational age stereotyping. Based on a biographical-narrative approach, participants (secondary school students and nursing home residents) were invited to share ideas about existential questions of life (e.g., about one’s core experiences, future plans, and personal values). Therefore, the dyadic Life Story Interview had been translated into a group format (the Life Story Encounter Program, LSEP), consisting of ten 90-minute sessions. Analyses verified that LSEP participants of both generations showed more favorable cross-generational age stereotypes immediately after, but also three months after the program end. Such change in age stereotyping was absent in a control group (no LSEP participation). The LSEP-driven short- and long-term effects on age stereotyping could be partially explained by two program benefits, the feeling of comfort with and the experience of learning from the other generation.